2014
DOI: 10.18632/oncotarget.2016
|View full text |Cite
|
Sign up to set email alerts
|

XIAP inhibitors induce differentiation and impair clonogenic capacity of acute myeloid leukemia stem cells

Abstract: Acute myeloid leukemia (AML) is a neoplasia characterized by the rapid expansion of immature myeloid blasts in the bone marrow, and marked by poor prognosis and frequent relapse. As such, new therapeutic approaches are required for remission induction and prevention of relapse. Due to the higher chemotherapy sensitivity and limited life span of more differentiated AML blasts, differentiation-based therapies are a promising therapeutic approach. Based on public available gene expression profiles, a myeloid-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…However, this study did not include CCC in the PXD arm and the anti-tumor activity of PXD in CCC has not been clarified. In addition, embelin, another XIAP inhibitor, has shown anti-cancer activity in experimental models of several cancers (10)(11)(12)(13), but experiments targeting ovarian CCCs have not been reported.…”
mentioning
confidence: 99%
“…However, this study did not include CCC in the PXD arm and the anti-tumor activity of PXD in CCC has not been clarified. In addition, embelin, another XIAP inhibitor, has shown anti-cancer activity in experimental models of several cancers (10)(11)(12)(13), but experiments targeting ovarian CCCs have not been reported.…”
mentioning
confidence: 99%
“…Interestingly, XIAP confers resistance to cancer therapy and cell survival (28,29). Notably, XIAP inhibitors have shown promising outcomes in cancer therapy, including acute myeloid leukemia (30). We found that XIAP was upregulated in the synovial tissues of patients with RA; this was inversely proportional to miR-431-5p levels.…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that XIAP expression is elevated in numerous types of cancer (18)(19)(20)(21). Thus, the downregulation of XIAP is recognized as a potential anticancer approach (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%